Teaching Performance Instruments of Physical Education Teachers - Lumba, Andreas J. F.; Blegur, Jusuf; Bayu, Wahyu Indra (Journal of Education Reseach and Evaluation, 2021)
A teacher's teaching performance will determine the success of learning. However, the main problem in developing teacher teaching performance lies in the "complex" instrumentation. Sometimes not very objective when doing the evaluation. In addition, the research instrument used was not specifically used to measure the teaching performance of physical education teachers. One of the teaching performance instruments relevant to physical education learning is the instrument developed by Maksum in 2012. This study aims to test the validity and reliability of Maksum's teaching performance instrument. This study involved 42 physical education teachers from basic education units to senior high schools determined by the accidental sampling technique. The instrument used is an observation guide developed by Maksum (2012), consisting of 19 statement items disseminated using google form. Test the validity and reliability using descriptive analysis, product-moment correlation, and Cronbach alpha. The study results were that all items of teaching performance instrument statements were valid (˃0.304) with the highest level of reliability (0.971). It can be said that this instrument can measure the teaching performance of physical education teachers. The research implication is that evaluators and teachers can use this instrument to assess and improve their teaching performance.